2009
DOI: 10.1152/ajpcell.00504.2008
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor induces protein kinase D-dependent production of proinflammatory cytokines in endothelial cells

Abstract: Emerging evidence indicates that vascular endothelial growth factor (VEGF) plays a critical role in host inflammatory responses in several disease states, including atherosclerosis, sepsis, and rheumatoid arthritis. In this study, we determined the effect of VEGF on endothelial induction of proinflammatory cytokines and investigated the responsible signal pathways. By using a cytokine antibody array that detects the end point protein products released from endothelial cells (ECs), we found that VEGF, via VEGF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 40 publications
2
51
0
4
Order By: Relevance
“…VEGF via VEGF receptor2 predominantly induces the production of pro-inflammatory cytokines IL-6, IL-8 and growth related oncogene-alpha in endothelial cells. So, this explains a new insight into the mechanism of the proinflammatory activity of VEGF in host inflammatory responses in several disease states [26].…”
Section: Fibrosismentioning
confidence: 86%
See 1 more Smart Citation
“…VEGF via VEGF receptor2 predominantly induces the production of pro-inflammatory cytokines IL-6, IL-8 and growth related oncogene-alpha in endothelial cells. So, this explains a new insight into the mechanism of the proinflammatory activity of VEGF in host inflammatory responses in several disease states [26].…”
Section: Fibrosismentioning
confidence: 86%
“…VEGF via VEGF receptor2 predominantly induces the production of pro-inflammatory cytokines IL-6, IL-8 and growth related oncogene-alpha in endothelial cells. So, this explains a new insight into the mechanism of the proinflammatory activity of VEGF in host inflammatory responses in several disease states [26].Arsenicosis is a multisystem disorder that has been linked to hyperkeratosis and skin cancer. Cutaneous toxicity is a related effect of various cytokines like IL-8, TGF-β, TNF-α and GM-CSF.…”
mentioning
confidence: 92%
“…1D). Gö6976 is an inhibitor of PKD and classical PKC isoforms and has been widely used as a PKD inhibitor for intact cell studies (29,44,45). These findings indicate that inhibition of PKD activity increases TEER of 16HBE14oϪ cell monolayers and suggest that PKD may be a negative regulator of epithelial barrier integrity.…”
Section: Inhibition Of Pkd Activity or Silencing Of Pkd Increase Teermentioning
confidence: 87%
“…These findings suggest a functional differentia among PKD isoforms. We have reported that PKD1 regulates the production of proinflammatory cytokines by vascular endothelial growth factor (VEGF) in endothelial cells (29) and that PKD2 is pivotal for angiogenesis (30). We also found that both PKD2 and PKD3 were novel growth regulators in triple-negative breast cancer cells (31).…”
mentioning
confidence: 99%
“…30 We believe that thrombosis may be the stimulating agent for the increased levels of both chemokines. Moreover, previous reports have shown that retinal ischaemia stimulates IL-8 and MCP-1 production, and both chemokines are involved in retinal neovascularization.…”
Section: Il-8 and Mcp-1 In Brvo Macular Oedemamentioning
confidence: 94%